2019
DOI: 10.1038/s41598-019-56831-y
|View full text |Cite
|
Sign up to set email alerts
|

Levosimendan and systemic vascular resistance in cardiac surgery patients: a systematic review and meta-analysis

Abstract: Levosimendan is a potent non-adrenergic inodilator agent. The net effect of hemodynamic changes may result in a hyperdynamic state with low systemic vascular resistance. We conducted a systematic review and meta-analysis assessing hemodynamics in cardiac surgery patients treated with levosimendan. English-language literature was searched systematically from 2006 until October 2018, including randomized controlled trials and case-matched or retrospective studies providing at least two sequentially measured hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Separately, Terbeck and colleagues, arguing from the premise that patients with heart failure may be especially susceptible to the vasodilatory effects of drugs, explored whether the use of levosimendan increases the risk of vasoplegic syndrome (i.e., severe refractory hypotension and low systemic vascular resistance in the absence of a low cardiac output [CO] state) in patients undergoing cardiac surgery with attendant cardiopulmonary bypass (CPB) [ 7 ]. All but one of the 16 included studies (14 RCTs plus two other published studies) examined the use of preoperatively administered levosimendan.…”
Section: Postoperative Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Separately, Terbeck and colleagues, arguing from the premise that patients with heart failure may be especially susceptible to the vasodilatory effects of drugs, explored whether the use of levosimendan increases the risk of vasoplegic syndrome (i.e., severe refractory hypotension and low systemic vascular resistance in the absence of a low cardiac output [CO] state) in patients undergoing cardiac surgery with attendant cardiopulmonary bypass (CPB) [ 7 ]. All but one of the 16 included studies (14 RCTs plus two other published studies) examined the use of preoperatively administered levosimendan.…”
Section: Postoperative Settingsmentioning
confidence: 99%
“…d) Focus on eight therapeutic settings of intensive care unit (ICU) and emergency medicine (EM), excluding hospitalization for AHF or advanced heart failure (because described in a separate update [3]). The selected areas are (1) postoperative settings, (2) septic shock, (3) weaning from ventilator, (4) weaning from veno-arterial extracorporeal membrane oxygenation (VA-ECMO), ( 5) cardiogenic shock, (6) Takotsubo syndrome (TTS), (7) acute cardiac care complicated by renal dysfunction/failure, and (8) pulmonary hypertension (PH) and right ventricular dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis including 16 studies found no evidence that levosimendan produces vasopressor-resistant vasoplegic syndrome [ 26 ]. Our results are consistent with this finding, since only 25.7% of all patients required addition of norepinephrine for a median period of 12 h. The prevalence of hypotension in our cohort was 36.2% (very common), a figure that is less than the 50% observed in the REVIVE II trial [ 27 ] despite the fact that we included all hypotensive episode occurring up to 6 days after levosimendan initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite an improvement in ventricular function, levosimendan does not increase myocardial oxygen uptake significantly. An increase in coronary blood flow and a reduction in coronary vascular resistance have been observed (5). Common adverse effects reported are hypotension, headache, and dizziness secondary to the vasodilating properties.…”
Section: Introductionmentioning
confidence: 99%